Prototipe Smart Helmet dengan Notifikasi Navigasi Real-Time melalui Koneksi WiFi - Adrian Febriansyah; Irman Hariman (Universitas Kebangsaan Republik Indonesia, 2025)
The development of wearable technology has brought various innovations to improve rider safety and comfort. One such innovation is a smart helmet capable of displaying real-time navigation notifications. This research aims to design and implement a smart helmet prototype integrating an ESP32 microcontroller and an OLED display, utilizing a Wifi connection to receive navigation data from an Android smartphone. The method used was prototyping, encompassing literature review, system design, hardware and software development, and questionnaire testing. The implementation results showed that the smart helmet successfully displayed turn direction information in the form of symbols in real time, thus helping motorcyclists stay focused while driving. The Wifi connection proved stable in transmitting data, although there were limitations in displaying route details due to software integration constraints. Overall, this research demonstrates that smart helmets have significant potential to improve safety, especially for highly mobile riders.